Usage-based prosody: towards the analysis of sociolinguistic and geolectal patterns in two case studies - Martín Butragueño, Pedro; Velásquez Upegui, Eva Patricia (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper presents two case studies from a use-based prosody perspective, based on sociolinguistic interviews of the "Project for the study of Spanish in Spain and America" ​​carried out in several cities (Guatemala City, Mexico City, Havana, Lima, Madrid, Monterrey, Montevideo, and Santiago de Chile). In the first study, the performance of broad-focus statements nuclear configurations in six cities is compared. In the second, the potential of the referred speech to analyze various characteristics of speech prosody is considered. The first case study suggests the existence of two main geoprosodic patterns, in addition to the existence of some social effects. The second case study emphasizes the importance of pragmatic-discursive tasks over other types of effects. In conclusion, the interest in analyzing the prosody in use is underlined, compared to other perspectives in which there is a tendency to work with isolated utterances.
Keywords: intonation; geoprosody; socioprosody; speech prosody